ANALISIS IMPLEMENTASI LAYANAN PICK UP SERVICES UNTUK MENINGKATKAN MOTIVASI NASABAH MENABUNG DI BMT AL-HIJRAH BUKITTINGGI - Honi Arsita; Dewi Manda Anggraini (CV. Adiba Aisha Amira, 2025)
This study was motivated by the fear and doubt of customers to bring large amounts of money to BMT Al- Hijrah Bukittinggi, fear of problems on the way to BMT Al- Hijrah Bukittinggi. Thus, this study aims to determine the impact and implementation of pick- up services in increasing customer savings motivation at BMT Al- Hijrah. This study uses a descriptive qualitative method, namely research that describes data and information in the field based on facts obtained through interviews and observations with sources. The informants in this study were staff and customers of BMT Al- Hijrah Bukittinggi. While the data analysis used was wrong with data reduction techniques, data presentation, and drawing conclusions. The research was conducted from September 13, 2024 to October 2024. Based on the research that has been done, it can be concluded that the pick- up services provided by BMT Al- Hijrah Bukittinggi influence customers' decisions to save. This is shown by the large response of BMT Al Hijrah Bukittinggi customers who have a high average service level value, thus supporting that the service provided to customers will have a positive influence on customer decisions later. BMT Al Hijrah Bukittinggi has also improved the quality of pick up service through indicators of service quality success such as, evidence of financial, reliability, responsiveness, guarantees, and empathy. The optimal implementation of all indicators of service quality success will increase customer trust and interest in saving at BMT Al Hijrah Bukittinggi. Good service will be able to form a positive attitude in the early stages of customers towards the BAIT Al Hijrah Bukittinggi institution. This positive attitude is formed on the basis of customer satisfaction which will consistently cause interest in using the products and services offered which in the end customers will decide to become permanent customers at BMT Al Hijrah Bukittinggi.